If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = 6y + -11 Reorder the terms: -1 = -11 + 6y Solving -1 = -11 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -1 + -6y = -11 + 6y + -6y Combine like terms: 6y + -6y = 0 -1 + -6y = -11 + 0 -1 + -6y = -11 Add '1' to each side of the equation. -1 + 1 + -6y = -11 + 1 Combine like terms: -1 + 1 = 0 0 + -6y = -11 + 1 -6y = -11 + 1 Combine like terms: -11 + 1 = -10 -6y = -10 Divide each side by '-6'. y = 1.666666667 Simplifying y = 1.666666667
| 5/13x=25 | | 4x-7(3-3x)-9=x | | 7x+7=3x-5 | | 3m-6n=9n+12 | | -b+17= | | 3x-4y+8=26 | | 7+3t=(6-t)/2 | | a^2+3x=2a^2 | | -3(v-3)=3v-33 | | 12x=3y+6 | | -6a(-5)(2b)= | | 2x+3=57 | | 5(r-3)-2r=-30 | | Y-5=mx-2 | | 5t+3=-12 | | -10b+3(-1+b)= | | 8x-5/12=13/18 | | 8(7-p)-8=-16 | | 4x-18+8x=7x+3x+8 | | -3+n=6n+22 | | 3(x-2)=5x+4 | | 1/3x+15=20 | | 4x-2+5x+10+2x+14=0 | | 2x+3=60 | | 2x+5=3x+20 | | -x+11/12=-5/12 | | 1/3(6-15w)=3/8(40w-8) | | -x/2=-6 | | 12y=5y+42 | | 1/2y=1/3y+2 | | 14x+4=9x+7 | | 9y=4y+120 |